2010
DOI: 10.1302/0301-620x.92b8.24194
|View full text |Cite
|
Sign up to set email alerts
|

Optimal acetabular orientation for hip resurfacing

Abstract: Pseudotumours are a rare complication of hip resurfacing. They are thought to be a response to metal debris which may be caused by edge loading due to poor orientation of the acetabular component. Our aim was to determine the optimal acetabular orientation to minimise the risk of pseudotumour formation. We matched 31 hip resurfacings revised for pseudotumour formation with 58 controls who had a satisfactory outcome from this procedure. The radiographic inclination and anteversion angles of the acetabular compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 42 publications
9
122
0
Order By: Relevance
“…1,3,11,[13][14][15][16][17][18][19][20] The higher revision rate in women can be attributed partly to the differences in the proportion of men and women who receive smaller femoral heads. Data from the Australian registry show that after adjusting for femoral head size, female gender no longer remained an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,11,[13][14][15][16][17][18][19][20] The higher revision rate in women can be attributed partly to the differences in the proportion of men and women who receive smaller femoral heads. Data from the Australian registry show that after adjusting for femoral head size, female gender no longer remained an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5 In addition, high levels of circulating metal ions and reactive lesions have been identified in some patients. [6][7][8][9][10] Suboptimal acetabular component positioning has been recognised as an important factor in failure of HRA, 5,6,11 leaving little margin of error for the surgeon as far as implantation of the acetabular component is concerned. These factors have led to a decrease in the number of HRAs performed annually in recent years.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…8 of the 10 patients had well positioned components according to AP radiographs though we were unable to measure anteversion at the time. It would be useful to revisit these cases to remeasure inclination and anteversion with the latest validated software such as EBRA [38].…”
Section: Metal On Metal Hips and Squeakingmentioning
confidence: 99%
“…[1][2][3][4][5][6] Therefore, it is recommended that in modern THA with a conventional femoral head size, [7] surgeons use an inclination of [40][41][42][43][44][45] and anteversion based on combined anteversion theory for acetabular cup orientation, and indeed it has recently been reported that precise implantation prevents such complications. [8,9] Although many helpful techniques have been developed to achieve accurate implantation, [8][9][10][11][12][13][14] such as computed tomographybased (CT-based) navigation, imageless navigation, and patient-specific surgical guides, it is also important to assess postoperative implant orientation and the accuracy of these estimation modalities.…”
Section: Introductionmentioning
confidence: 99%